2003
DOI: 10.1016/s0194-5998(03)00637-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of aging and hearing loss on distortion product otoacoustic emissions

Abstract: The use of DPOE measures for screening and monitoring cochlear status of adult women should take into account the age, pure-tone thresholds, and noise exposure status of the subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…DPOAEs are believed to reveal subtle cochlear changes that may be overlooked by audiometry. 30,31 Studies show that aging males experience greater decreases in DPOAEs amplitudes compared to aging females. This decrease in DPOAEs is often proportional to the degree of hearing loss.…”
Section: Vestibular Systemmentioning
confidence: 99%
“…DPOAEs are believed to reveal subtle cochlear changes that may be overlooked by audiometry. 30,31 Studies show that aging males experience greater decreases in DPOAEs amplitudes compared to aging females. This decrease in DPOAEs is often proportional to the degree of hearing loss.…”
Section: Vestibular Systemmentioning
confidence: 99%
“…8 The results of the present study showed a general decrease in SOAE levels with age, but not a consistent and uniform decrease in all SOAE levels as was the case for SOAE frequency. Studies on evoked OAE levels as a function of age in adults show little consensus in the results ͑e.g., Cilento et al, 2003͒. Some studies show a decrease in OAE levels with age, which are independent of changes in hearing threshold, and others do not.…”
Section: A Long-term Frequency Shiftsmentioning
confidence: 99%
“…DPOAE are reduced or absent when the mobility of the OHC, which is the source of OAE generation, is impaired by damage to those cells 15 . Some previous studies demonstrated that DPOAE incidence greatly differed depending on age 16 gender and hearing level.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction in OAE is known to follow decreased task of the stria vascularis and to follow hair cell loss 16 . Consequently, as audiometric thresholds worsen, the amplitude of the DPOAE response decreases and finally disappears 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation